2015
DOI: 10.1186/s12879-015-1297-x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid dissemination of colistin and carbapenem resistant Acinetobacter baumannii in Central Greece: mechanisms of resistance, molecular identification and epidemiological data

Abstract: BackgroundColistin-resistant/carbapenem-resistant Acinetobacter baumannii is a significant challenge for antibiotic treatment and infection control policies. Since 2012, in Central Greece an increase of colistin/pan- resistant A. baumannii has occurred, indicating the need for further analysis.MethodsA total of 86 colistin-resistant/carbapenem-resistant out of 1228 A. baumannii clinical isolates, consecutively collected between 2012 and 2014 in a tertiary Greek hospital of Central Greece, as well as one enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 39 publications
6
63
3
2
Order By: Relevance
“…These strains tend to be pan-resistant, with no available antibiotic therapies left. Tigecycline resistance now exceeds 50% in some regions, and polymyxin resistance rates as high as 20% have been seen in Greece, and are increasingly reported in other regions as well (189,249,(264)(265)(266). These pan-resistant isolates underscore the critical need to identify alternative therapeutic strategies.…”
Section: Current Treatment Optionsmentioning
confidence: 99%
“…These strains tend to be pan-resistant, with no available antibiotic therapies left. Tigecycline resistance now exceeds 50% in some regions, and polymyxin resistance rates as high as 20% have been seen in Greece, and are increasingly reported in other regions as well (189,249,(264)(265)(266). These pan-resistant isolates underscore the critical need to identify alternative therapeutic strategies.…”
Section: Current Treatment Optionsmentioning
confidence: 99%
“…Giani et al [4] have reported an outbreak of colistinresistant KPC-producing K. pneumoniae in 93 patients over 4 years from 2009 to 2012. In one of the surveillance studies between 2012 to 2014 in Greece, 86 colistin-resistant/carbapenem-resistant clinical isolates were reported [14]. Likewise, outbreaks of colistin-resistant, carbapenem-resistant Enterobacteriaceae cases have been reported worldwide including Israel involving 15 patients over 10 months in 2006 [15], South Korea [5], and Detroit [16].…”
Section: Discussionmentioning
confidence: 99%
“…Giamarellou ('Epidemiology of infections caused by polymyxin-resistant pathogens') reviews the recent literature on the epidemiology of infections due to polymyxin-resistant Gram-negative bacteria in humans [8]. Polymyxin-resistant pathogens in clinical settings, such as Klebsiella pneumoniae and A. baumannii, may be concomitantly resistant to carbapenems [9,10]. New perspectives on how to safeguard polymyxins (e.g.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%